Personal Branding through Da'wah on TikTok Social Media - Amirah Nabilah; Bhunga Aulia; Dwi Yuniar (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2021)
The COVID-19 pandemic that has hit the world requires people to stay at home, making social media the choice of people to seek entertainment or share knowledge. TikTok is one of the interesting centers for preachers to do their preaching. This study discussed Personal Branding on Husain Basyaiban @basyasman00 account through TikTok social media intending to be achieved by researchers is to find out how personal branding Husain Basyaiban through three da'wah content with the highest viewers on social media TikTok. Husain is a person with successful personal branding through the social media networking platform TikTok, where he presents content about Islamic Da'wah. Based on this, the research team was interested in analyzing how the personal branding process carried out by Husain Basyaiban through Da'wah on the social media platform TikTok. This research uses a qualitative approach with a data collection method in the form of document study, resulting in descriptive data in the form of written words from the behavior studied. The results of the research showed that Husain Basyaiban can meet 11 Criteria for Effective Authentic Personal Branding, namely Authenticity, Integrity, Consistency, Specialization, Authority, Privileges, Relevant, Perseverance, Visibility, Good Deeds, Performance.